A preparation method of IL@MIL-101 material and its application in CO2 separation

By encapsulating [P4442]n[X] ionic liquid in MIL-101, the [P4442]n[X]@MIL-101 composite material is prepared, which solves the shortcomings of existing materials in CO2 adsorption and separation and achieves high CO2 adsorption capacity and selectivity, suitable for CO2 capture and separation.

CN115957723BActive Publication Date: 2025-01-21ZHEJIANG SCI-TECH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211356882.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-01
Publication Date
2025-01-21
Estimated Expiration
2042-11-01

AI Technical Summary

Technical Problem

The existing ionic liquids and metal organic frame materials have problems such as limited adsorption sites, small absorption mass fraction, increased viscosity, low mass transfer rate and low adsorption amount under low CO2 partial pressure conditions.

Method used

By encapsulating [P4442]n[X] ionic liquid in MIL-101, we prepare [P4442]n[X]@MIL-101 composite materials, adjust the gas affinity of MOFs, create new adsorption sites, and improve CO2 isosteric adsorption heat and selectivity.

Benefits of technology

It achieves high CO2 adsorption capacity and high stability under normal pressure. The CO2 adsorption capacity reaches 65cm3/g, the selectivity is enhanced, and the adsorption process is reversible. It is suitable for CO2 capture and CO2/N2 gas separation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115957723B_ABST
    Figure CN115957723B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of composite material preparation and application, and provides a method for preparing an IL@MIL-101 composite material and a method for preparing an IL@MIL-101 composite material in CO 2 The preparation method comprises: S1, exchanging tributyl ethylphosphonium bromide solution with alkaline ion exchange resin to obtain [P 4442 ][OH] aqueous solution; S2, the obtained [P 4442 ][OH] aqueous solution and organic acid H n X was neutralized, stirred for a period of time, and then rotary evaporated and dried to obtain [P 4442 ] n [X] ionic liquid; S3, disperse MIL-101 in the solvent, add [P 4442 ] n [X] The ionic liquid is mixed, stirred for a period of time, and centrifuged to dry to obtain the IL@MIL-101 material. The ionic liquid in the method of the present invention has a wide range of choices and is suitable for CO 2 Capture of CO 2 / N 2 Gas separation has strong universality; the preparation method is simple, the operation is simple and fast, it is green and environmentally friendly, and the cost is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite material preparation and application, and in particular to a method for preparing an IL@MIL-101 composite material and a method for preparing the same in CO 2 Separation application. Background Art

[0002] With the continuous development of global industrialization, the large-scale combustion of fossil fuels has led to the increase of CO 2 The concentration is rising, leading to the greenhouse effect and climate change. How to capture CO in the air efficiently and with low energy consumption 2 It has become the focus of research at home and abroad. Compared with the conventional absorption separation and enrichment of CO 2 Compared with other technologies, the adsorption method is regarded as a CO2 removal method with great industrial application prospects due to its advantages such as low corrosion, low energy consumption and strong compatibility with existing equipment. 2 Separation technology.

[0003] Among many adsorbents, ionic liquids (ILs) have become a popular choice for CO adsorption due to their extremely low saturated vapor pressure, excellent thermal stability, and adjustable structure. 2 The research on absorbents is hot, but the absorption sites of ionic liquids are limited, the absorption mass fraction is small, and the viscosity of ionic liquids increases sharply after absorption, forming a huge hydrogen bond network. The viscosity increases by 240 times after absorption, which seriously affects the gas absorption and mass transfer rate. The high viscosity and low diffusion coefficient of ionic liquids lead to unsatisfactory effects in the absorption and separation of carbon dioxide. MIL-101 has the advantages of large specific surface area and high stability. It has extraordinary advantages in the fields of adsorption and separation, but pure MOF materials have a low affinity for CO2. 2 The adsorption belongs to physical adsorption. 2 The adsorption capacity is low under partial pressure conditions, and the selective separation is difficult, making it difficult to achieve CO 2 of capture.

[0004] Currently reported applications in CO 2 There are many materials for adsorption separation. Alper Uzun et al. proposed a core new concept - a shell-type ionic liquid / metal organic framework (IL / MOF) composite. The hydrophilic IL, 1-(2-hydroxyethyl)-3-methylimidazolium dicyanamide, [HEMIM][DCA], was deposited on the hydrophobic zeolitic imidazole framework ZIF-8. Compared with the parent MOF, the composite had a CO absorption capacity of 1 mbar and 25 °C. 2 The absorption is about 5.7 times that of CO 2 / CH 4The selectivity is about 45 times [MuhammadZeeshan,Vahid Nozari,M.Baris Yagci,TugbaIs1k,UgurUnal,VolkanOrtalan,SedaKeskin,andAlperUzun.Core-Shell Type Ionic Liquid / Metal Organic FrameworkComposite:AnExceptionallyHighCO 2 / CH 4 Amr Henni et al. studied the carbon dioxide (CO) reaction of ZIF-8 impregnated with ionic liquid 1-butyl-3-methylimidazolium acetate [Bmim][Ac] 2 ) capture performance, which is the CO 2 Absorption and CO 2 / N 2 The selectivity of [Bmim][Ac]@ZIF-30 is significantly higher than that of the original ZIF-8. 2 The capacity is 7 times higher than that of the original ZIF-8 [Mohanned Mohamedali, Hussameldin, Ibrahim, Amr Henni. Incorporation of acetate-based ionic liquids into azeolitic imidazolate framework (ZIF-8) as efficient sorbents for carbon dioxide capture. Chemical Engineering Journal. 2018, 334, 817-828]. However, the adsorption performance of the above materials still needs to be improved. Therefore, a novel material with high CO 2 The adsorption capacity of IL-MOF composites remains a great challenge. Summary of the invention

[0005] The present invention aims to overcome the above-mentioned shortcomings and deficiencies of the prior art and provide a high CO 2 The purpose of the present invention is achieved based on the following technical solutions:

[0006] The first aspect of the present invention provides a method for preparing an IL@MIL-101 material, comprising the following steps:

[0007] S1, the tributyl ethylphosphonium bromide solution is exchanged through an alkaline ion exchange resin to obtain [P 4442 ][OH] aqueous solution;

[0008] S2, the obtained [P 4442 ][OH] aqueous solution and organic acid H n X was neutralized, stirred for a period of time, and then rotary evaporated and dried to obtain [P 4442 ] n [X] ionic liquids;

[0009] S3, disperse MIL-101 in the solvent, add [P 4442 ] n [X] The ionic liquids are mixed, stirred for a period of time, and centrifuged to dry to obtain the IL@MIL-101 material.

[0010] This patent will [P 4442 ] n [X] Ionic liquid encapsulated in MIL-101 to prepare [P 4442 ] n [X]@MIL-101 composite material, which has high CO at normal pressure 2 With the characteristics of adsorption capacity and high stability, ionic liquids are added as guest molecules into the pores of MOFs to adjust the gas affinity of MOFs. With the introduction of IL, the porosity of MOF can be adjusted, new adsorption sites can be created, and the molecular sieve performance of MOF can be improved. With the incorporation of IL, CO 2 The isosteric adsorption heat changes more obviously, resulting in CO 2 The selectivity is enhanced, thus significantly increasing CO 2 Adsorption amount.

[0011] Preferably, step S1 is specifically: passing the tributyl ethylphosphonium bromide solution through an alkaline ion exchange resin column, with the effluent rate being 2-3 seconds per drop, collecting the effluent, and stopping the collection when the effluent becomes weakly alkaline, and the resulting solution is [P 4442 ][OH] aqueous solution.

[0012] Preferably, the concentration of the tributyl ethylphosphonium bromide solution in step S1 is 0.5-2.5 g / mL, and the alkaline ion exchange resin is 550A (OH) anion exchange resin.

[0013] Preferably, the preparation method of the ionic liquid in step S2 is: 4442 The concentration of [OH] aqueous solution was calibrated with potassium hydrogen phthalate standard solution and the [P 4442 ][OH], adding organic acid H n X and [P 4442][OH] undergoes complete acid-base neutralization reaction, and after stirring, rotary evaporation and drying, [P 4442 ] n [X] ionic liquid; the organic acid H n X includes iminodiacetic acid, aminotriacetic acid or an amino acid.

[0014] Preferably, the amino acid comprises glycine, alanine, proline, serine, threonine, tryptophan or phenylalanine.

[0015] Preferably, in step S2: the stirring temperature is 10-40°C, the stirring time is 10-36h, the rotary evaporation temperature is 60-85°C, and the drying temperature is 60-110°C.

[0016] Preferably, the solvent in step S3 includes one or more of water, ethanol, N,N-dimethylformamide, cyclohexane, methanol, toluene, dichloromethane, tetrahydrofuran, and ethyl acetate.

[0017] Preferably, in step S3, 4442 ] n [X] The dosage ratio of ionic liquid to MIL-101 is 0.3-1.2 mol / g.

[0018] Preferably, in step S3, the ionic liquid is dissolved in the solvent by ultrasound, and the ultrasound time is 5 to 30 minutes.

[0019] Preferably, in step S3: the stirring temperature is 10-40°C, the stirring time is 10-36h, and the drying temperature is 60-110°C.

[0020] The second aspect of the present invention provides an IL@MIL-101 material obtained according to the above preparation method.

[0021] The third aspect of the present invention provides an application of an IL@MIL-101 composite material in carbon dioxide adsorption separation.

[0022] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0023] 1. The present invention adopts a stirring centrifugal method to place a functionalized ionic liquid in the MOFs pores for confinement, so that the IL@MOF composite material has a specific selectivity, and IL@MIL-101 is used for the adsorption and separation of carbon dioxide. The ionic liquid-metal organic framework composite material prepared by this method has the advantages of more dispersed particles, adjustable particle size and loading capacity compared to the composite material prepared by the impregnation method, and has good practical application value.

[0024] 2. The IL@MIL-101 material prepared by the present invention is 2 It has excellent adsorption performance in terms of adsorption separation, and the adsorption capacity of carbon dioxide can reach 65cm 3 / g; compared with other IL@MOF materials, it has a larger adsorption capacity and strong applicability. The present invention can be desorbed at 0.1 atmospheres, and has good stability. After five adsorption and desorption cycles, the original adsorption capacity can still be maintained.

[0025] 3. The ionic liquid of the present invention has a wide selection range and is suitable for CO 2 Capture of CO 2 / N 2 Gas separation has strong universality; the preparation method is simple, the operation is simple and fast, it is green and environmentally friendly, and the cost is low. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The XRD patterns of the materials obtained in Example 1 and Comparative Example 1 are shown below;

[0027] Figure 2 The SEM images of the materials obtained in Example 1 and Comparative Example 1 are as follows: (a) MIL-101, (b) 1#[P 4442 ] 2 [IDA]@MIL-101;

[0028] Figure 3 The materials obtained in Example 1 and Comparative Example 1 were subjected to CO 2 Performance diagram in adsorption. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] In the preferred embodiment of the present invention, MIL-101 is prepared by the method of the literature:

[0031] Cr(NO 3 ) 2 9H 2O (2g, 5mmol), terephthalic acid (0.823g, 5mmol), hydrofluoric acid (48wt%, 5mmol) and deionized water (24mL) were added to the lining of the reactor, and placed in an oven after ultrasonic treatment for 30min, heated to 220℃ at a heating rate of 1℃ / min, kept at a constant temperature for 8h, cooled to 150℃ after 1h, and then slowly cooled to room temperature after 12h. The resulting solution was filtered using a G2 funnel to remove unreacted terephthalic acid crystals, and the filtrate was filtered using a G4 funnel to obtain a green powder, which was washed with deionized water and ethanol many times, and then dispersed in a 95% ethanol solution, placed in a reactor and placed in an oven at 80℃ for 24h. Filter while hot to obtain MIL-101 material. Finally, MIL-101 was vacuumed at 150℃ for 12h and activated for use.

[0032] The alkaline ion exchange resin used in the preferred embodiment of the present invention is 550A (OH) anion exchange resin.

[0033] Example 1

[0034] A method for preparing an IL@MOF composite material comprises the following steps:

[0035] (1) Weigh [P 4442 [Br] (20 g) was dissolved in distilled water and ion exchanged with alkaline ion exchange resin to obtain [P 4442 ][OH] solution and calibrated with potassium hydrogen phthalate [P 4442 ][OH] concentration of the alkaline solution; take 2mmol[P 4442 ][OH] and 1mmol H 2 IDA was neutralized, stirred at room temperature for 24 h, and a large amount of water was removed by rotary evaporation at 75 °C, and then placed in an oven at 80 °C for 48 h to obtain [P 4442 ] 2 [IDA];

[0036] (2) Disperse MIL-101 (200 mg) in methanol and add [P 4442 ] 2 [IDA] (100 mg), ultrasonically treated for 15 min, stirred at room temperature for 24 h, centrifuged to obtain a solid, and dried under vacuum at 80 °C to obtain [P 4442 ] 2 [IDA]@MIL-101.

[0037] Example 2

[0038] A method for preparing an IL@MOF composite material comprises the following steps:

[0039] (1) Weigh [P 4442[Br] (20 g) was dissolved in distilled water and ion exchanged with alkaline ion exchange resin to obtain [P 4442 ][OH] solution, and use potassium hydrogen phthalate to calibrate the concentration of the alkaline solution; take 2mmol[P 4442 ][OH] and 1mmol H 2 IDA was neutralized, stirred at room temperature for 24 h, and a large amount of water was removed by rotary evaporation at 75 °C, and then placed in an oven at 80 °C for 48 h to obtain [P 4442 ] 2 [IDA];

[0040] (2) Disperse MIL-101 (200 mg) in methanol and add [P 4442 ] 2 [IDA] (75 mg), ultrasonically treated for 15 min, stirred at room temperature for 24 h, centrifuged to obtain a solid, and dried under vacuum at 80 °C to obtain [P 4442 ] 2 [IDA]@MIL-101.

[0041] Example 3

[0042] A method for preparing an IL@MOF composite material comprises the following steps:

[0043] (1) Weigh [P 4442 [Br] (20 g) was dissolved in distilled water and ion exchanged with alkaline ion exchange resin to obtain [P 4442 ][OH] solution, and use potassium hydrogen phthalate to calibrate the concentration of the alkaline solution; take 2mmol[P 4442 ][OH] and 1mmol H 2 IDA was neutralized, stirred at room temperature for 24 h, and a large amount of water was removed by rotary evaporation at 75 °C, and then placed in an oven at 80 °C for 48 h to obtain [P 4442 ] 2 [IDA];

[0044] (2) Disperse MIL-101 (200 mg) in methanol and add [P 4442 ] 2 [IDA] (125 mg), ultrasonically treated for 15 min, stirred at room temperature for 24 h, centrifuged to obtain a solid, and dried under vacuum at 80 °C to obtain [P 4442 ] 2 [IDA]@MIL-101.

[0045] Example 4

[0046] A method for preparing an IL@MOF composite material comprises the following steps:

[0047] (1) Weigh [P 4442 [Br] (20 g) was dissolved in distilled water and ion exchanged with alkaline ion exchange resin to obtain [P 4442 ][OH] solution, and use potassium hydrogen phthalate to calibrate the concentration of the alkaline solution; take 2mmol[P 4442 ][OH] and 1mmol H 2 IDA was neutralized, stirred at room temperature for 24 h, and a large amount of water was removed by rotary evaporation at 75 °C, and then placed in an oven at 80 °C for 48 h to obtain [P 4442 ] 2 [IDA];

[0048] (2) Disperse MIL-101 (200 mg) in methanol and add [P 4442 ] 2 [IDA] (150 mg), ultrasonically treated for 15 min, stirred at room temperature for 24 h, centrifuged to obtain a solid, and dried under vacuum at 80 °C to obtain [P 4442 ] 2 [IDA]@MIL-101.

[0049] Example 5

[0050] A method for preparing an IL@MOF composite material comprises the following steps:

[0051] (1) Weigh [P 4442 [Br] (20 g) was dissolved in distilled water and ion exchanged with alkaline ion exchange resin to obtain [P 4442 ][OH] solution, and use potassium hydrogen phthalate to calibrate the concentration of the alkaline solution; take 2mmol[P 4442 ][OH] and 1mmol H 2 IDA was neutralized, stirred at room temperature for 24 h, and a large amount of water was removed by rotary evaporation at 65 °C, and then placed in a 100 °C oven under vacuum and dried for 48 h to obtain [P 4442 ] 2 [IDA];

[0052] (2) Disperse MIL-101 (200 mg) in methanol and add [P 4442 ] 2 [IDA] (200 mg), ultrasonic for 15 min, stirred at room temperature for 24 h, centrifuged to obtain a solid, and dried under vacuum at 100 °C to obtain [ P4442 ] 2 [IDA]@MIL-101.

[0053] Example 6

[0054] A method for preparing an IL@MOF composite material comprises the following steps:

[0055] (1) Weigh [P 4442 [Br] (20 g) was dissolved in distilled water and ion exchanged with alkaline ion exchange resin to obtain [P 4442 ][OH] solution, and use potassium hydrogen phthalate to calibrate the concentration of the alkaline solution; take 1mmol[ P4442 ][OH] was neutralized with 1 mmol Gly, stirred at room temperature for 24 h, and a large amount of water was removed by rotary evaporation at 80 °C, and then placed in a vacuum oven at 90 °C for 24 h to obtain [ P4442 ][Gly];

[0056] (2) Disperse MIL-101 (200 mg) in methanol and add [P 4442 [Gly] (100 mg), ultrasonically treated for 15 min, stirred at room temperature for 24 h, centrifuged to obtain a solid, and dried under vacuum at 90 °C to obtain [P 4442 ][Gly]@MIL-101.

[0057] Example 7

[0058] A method for preparing an IL@MOF composite material comprises the following steps:

[0059] (1) Weigh [P 4442 [Br] (20 g) was dissolved in distilled water and ion exchanged with alkaline ion exchange resin to obtain [P 4442 ][OH] solution, and use potassium hydrogen phthalate to calibrate the concentration of the alkaline solution; take 3mmol [P 4442 ][OH] and 1mmol H 3 The reaction was neutralized by NTA, stirred at room temperature for 24 h, and a large amount of water was removed by rotary evaporation at 75 °C, and then placed in a vacuum oven at 70 °C for 24 h to obtain [P 4442 ] 3 [NTA];

[0060] (2) Disperse MIL-101 (200 mg) in methanol and add [P 4442 ] 3 [NTA] (100 mg), ultrasonically treated for 15 min, stirred at room temperature for 24 h, centrifuged to obtain a solid, and dried under vacuum at 70 °C to obtain [P 4442 ] 3 [NTA]@MIL-101.

[0061] Comparative Example 1

[0062] This comparative example is pure MIL-101 material without loaded ionic liquid.

[0063] Comparative Example 2

[0064] This comparative example was prepared by impregnation method. 4442 ] 2 [IDA]@MIL-101:

[0065] (1) Weigh [P 4442 [Br] (20 g) was dissolved in distilled water and ion exchanged with alkaline ion exchange resin to obtain [P 4442 ][OH] solution, and use potassium hydrogen phthalate to calibrate the concentration of the alkaline solution; take 2mmol[P 4442 ][OH] and 1mmol H 2 IDA was neutralized, stirred at room temperature for 24 h, a large amount of water was removed by rotary evaporation, and the mixture was placed in an oven at 80 °C and vacuum dried for 48 h to obtain [P 4442 ] 2 [IDA];

[0066] (2) Disperse MIL-101 (200 mg) in methanol and add [P 4442 ] 2 [IDA] (100 mg), ultrasonic for 15 min, stirred for 24 h, evacuated in an oil bath at 80 °C, and dried in vacuum at 80 °C to obtain [P 4442 ] 2 [IDA]@MIL-101.

[0067] Comparative Example 3

[0068] DETA-Cl@MIL-101(Cr):

[0069] Diethylenetriamine-based ionic liquids were incorporated into MIL-101(Cr) using a post-synthesis modification (PSM) method. First, an excess of DETA-Cl (0.5 g) was dissolved in 30 ml of ethanol. 1.0 g of activated MIL-101(Cr) powder was uniformly dispersed into the solution by ultrasonic treatment. The suspension was stirred at 30°C for 24 h, and then the solid was separated by centrifugation. The ionic liquid was washed with ethanol and the product (DETA-Cl@MIL-101(Cr)) was obtained after vacuum drying. [Chen, Chong; Feng, Nengjie; Guo, Qirui; Li, Zhong; Li, Xue; Ding, Jing; Wang, Lei; Wan, Hui; Guan, Guofeng.Surface engineering of achromium metal-organic framework with bifunctional ionic liquids forselective CO 2adsorption:Synergistic effect between multiple active sites.Journal of Colloid and Interface Science,2018,03,029]

[0070] Comparative Example 4

[0071] This comparative example is pure [P 4442 ] 2 [IDA] Ionic liquid material (same as Example 1).

[0072] The following are structural characterization and performance tests:

[0073] 1. Conduct XRD powder diffraction test and SEM test.

[0074] 1. XRD powder diffraction test results show that the X-ray powder diffraction results obtained in Example 1 and Comparative Example 1 are as follows: Figure 1 As shown by Figure 1 As can be seen from the results, the diffraction peak results of Example 1 and Comparative Example 1 are consistent, indicating that the skeleton structure of MIL-101 is not changed after loading the ionic liquid.

[0075] 2. SEM test results are as follows Figure 2 As shown, it can be seen from the results that Example 1 ( Figure 2 The sample morphology of (b) still maintains the MIL-101 ( Figure 2 From the hexagonal bipyramidal structure in (a), it can be seen that the incorporation of ionic liquid has no effect on the structure of MIL-101.

[0076] 2. The materials obtained in Examples 1-7 and Comparative Examples 1-3 were tested for carbon dioxide adsorption performance under the same conditions. The experimental results are listed in Figure 3 and Table 1.

[0077] Table 1

[0078]

[0079] It can be seen from the data in Table 1 that the [P 4442 ] 2 [IDA]@MIL-101 composite materials for CO 2 It has good adsorption and selectivity for CO 2 The adsorption capacity reaches 65cm 3 / g, compared with the reported comparative example 3, [P 4442 ] 2[IDA]@MIL-101 composite materials have stronger alkaline sites, which can undergo a completely reversible chemical reaction with the acidic carbon of carbon dioxide and have stronger carbon dioxide adsorption capacity. Figure 3 As shown in the figure, compared with MIL-101, the composite material prepared by the present invention has a better resistance to CO 2 The adsorption capacity is significantly improved, with good selectivity, which can be used to design adsorbents with excellent performance for selective capture of CO in air 2 , in order to meet environmental challenges. Compared with comparative example 4, comparative example 4 uses ionic liquid to absorb CO 2 , is an irreversible process, requires analysis, and cannot be desorbed; and the [P 4442 ] 2 [IDA]@MIL-101 composite material adsorbs CO 2 It is a reversible process. The present invention can desorb at 0.1 atmospheric pressure with good stability. After five adsorption and desorption cycles, the original adsorption amount can still be maintained.

[0080] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing IL@MIL-101 material, characterized in that: The following steps are involved: S1. Pass a 0.5-2.5 g / mL tributyl ethylphosphonium bromide solution through an alkaline ion exchange resin column, with the effluent rate being 2-3 seconds per drop, and collect the effluent. When the effluent becomes weakly alkaline, stop collecting, and the resulting solution is [P 4442 ][OH] aqueous solution; S2, the obtained [P 4442 ][OH] aqueous solution and organic acid H n X was neutralized, stirred for a period of time, and then rotary evaporated and dried to obtain [P 4442 ] n [X] ionic liquids; S3, disperse MIL-101 in the solvent, add [P 4442 ] n [X] The ionic liquids are mixed, stirred for a period of time, and centrifuged to dry to obtain the IL@MIL-101 material.

2. The method for preparing an IL@MIL-101 material according to claim 1, characterized in that: The alkaline ion exchange resin in step S1 is 550A (OH) anion exchange resin.

3. The method for preparing an IL@MIL-101 material according to claim 1, characterized in that: The preparation method of the ionic liquid in step S2 is: 4442 The concentration of [OH] aqueous solution was calibrated with potassium hydrogen phthalate standard solution and the [P 4442 ][OH], adding organic acid H n X and [P 4442 ][OH] undergoes complete acid-base neutralization reaction, and after stirring, rotary evaporation and drying, [P 4442 ] n [X] ionic liquid; the organic acid H n X includes iminodiacetic acid, aminotriacetic acid or an amino acid.

4. The method for preparing an IL@MIL-101 material according to claim 1, characterized in that: In step S2: the stirring temperature is 10-40°C, the stirring time is 10-36h, the rotary evaporation temperature is 60-85°C, and the drying temperature is 60-110°C.

5. The method for preparing an IL@MIL-101 material according to claim 1, characterized in that: In step S3: the solvent includes one or more of water, ethanol, N,N-dimethylformamide, cyclohexane, methanol, toluene, dichloromethane, tetrahydrofuran, and ethyl acetate; Said [P 4442 ] n [X] The dosage ratio of ionic liquid to MIL-101 is 0.3-1.2 mol / g.

6. The method for preparing an IL@MIL-101 material according to claim 1, characterized in that: In step S3: the [P 4442 ] n [X] The ionic liquid is dissolved in the solvent by ultrasound, the stirring temperature is 10-40°C, the stirring time is 10-36h, and the drying temperature is 60-110°C.

7. An IL@MIL-101 material, characterized in that: Obtained according to the preparation method described in any one of claims 1-6.

8. Use of the IL@MIL-101 material according to claim 7 in carbon dioxide adsorption separation.

Citation Information

Patent Citations

  • Cage diameter adjusting method of microporous material containing cage structures

    CN109847702A

  • Preparation method and application of metal organic framework-ionic liquid composite material

    CN111589422A